Occurrence and Health Relevance of Occupational Single-Shock Exposure of the Hand–Arm System—An Epidemiological Exploration - Elke Ochsmann; Alexandra Corominas Cishek; Uwe Kaulbars (Vibration, 2026)
Background: Single-shock exposure to the hand–arm system is a distinct form of occupational mechanical exposure that is rarely assessed separately from continuous vibration. Due to methodological challenges and the lack of standardized definitions, epidemiological evidence on its prevalence and health relevance remains limited. Objectives: This study aimed to explore the occurrence of occupational single-shock exposure in a general working population and to examine its association with self-reported hand–arm health problems. A secondary objective was to assess the usefulness of an exploratory ISCO-08-based job–exposure matrix (JEM). Methods: A cross-sectional survey was conducted among workers from diverse occupational backgrounds. Participants reported the use of predefined hand-held tools emitting single shocks, as well as additional tools identified via free text. Job titles were coded according to ISCO-08 and combined with expert-based exposure assessments to develop an exploratory JEM. Associations between exposure and health outcomes were analyzed descriptively and analytically in three exposure regression models. Results: Overall, 35% of participants (N = 162) reported occupational exposure to single shocks across a wide range of occupations, including technical and mixed-task jobs, indicating broader exposure than expected from ISCO-based classifications. Although exposure was generally of low to moderate intensity, it was associated with reported hand–arm health problems, particularly in distal regions (fingers, hand, and wrist (FHW); OR 4.32, 95% CI 1.38–13.44), where high forces seemed to be the main risk aspect (OR 6.26, 95% CI 1.67–23.50). Conclusions: Single-shock exposure appears to be common and may be associated with adverse hand–arm outcomes even at relatively low levels. The exploratory JEM was useful for identifying underestimated occupations and heterogeneity but cannot replace detailed task- or measurement-based assessment. Improved exposure definitions, assessment methods, and longitudinal studies in larger cohorts are needed to clarify health risks.